PI observer design for a class of nondifferentially flat systems - Flores-Flores, Juan-Pablo; Martinez-Guerra, Rafael (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a methodology and design of a model-free-based proportional-integral reduced-order observer for a class of nondifferentially flat systems. The problem is tackled from a differential algebra point of view, that is, the state observer for nondifferentially flat systems is based on algebraic differential polynomials of the output.
Keywords: model-free-base PI reduced-order observer; synchronization; nondifferentially flat system; algebraic observability condition; uniform ultimate boundedness